A Q-switched erbium-doped fiber laser with a graphene saturable absorber - Ismail, M.A.; Ahmad, F.; Harun, Sulaiman Wadi; Arof, Hamzah; Ahmad, Harith (IOP Publishing, 2013)
We demonstrate a simple, compact and low cost Q-switched erbium-doped fiber laser (EDFL) exploiting a graphene saturable absorber (GSA) for possible applications in metrology, sensing and medical diagnostics. The EDFL operates at 1560 nm with repetition rates of 31.3 kHz and 25 kHz with GSA1 and GSA2, respectively, at pump power of 120 mW. The repetition rate is smaller with a lower pump power. It has a pulse width of 7.5 μs and pulse energy of 43.7 nJ with GSA2 at 120 mW pump power. It is also observed that a thicker layer of graphene produces a Q-switched fiber laser with a lower pump threshold and a higher output energy, but smaller repetition rate and pulse width.